Preparation and Properties of Fluorinated Acrylic Latex Modified with Rosin. Issue 3 (August 2013) - Chen, Lijun; Jiang, Wei
The fluorinated acrylic latex modified by rosin was prepared successfully via semi-continuous seeded emulsion polymerization of methyl methacrylate (MMA), butyl acrylate (BA), dodecafluoroheptyl methacrylate (DFMA) and rosin in water phase initiated with potassium persulfate (KPS) and emulsified with the aid of mixed surfactants of SDBS and OP-10. The structure of the resultant latex is confirmed by Fourier transform infrared spectroscopy (FTIR) spectrum. The influences of the amount of rosin on the properties of the resultant latex and its film were investigated in detail. Results show that the conversion and gel percentage is decreased with an increase amount of rosin. However, the particle size and glass transition temperature are increased with the increase amount of rosin.